Effects of air pollutants and their interactive environmental factors on winter wheat yield. (10th July 2021) - Zhang, Tianning; Song, Hongquan; Zhou, Boyan; Wang, Lei; Yang, An; Wang, Tuanhui; Kong, Haijiang; Chen, Youmin; Zhou, Shenghui; Fu, Shenglei
Abstract: Quantifying the environmental determinants influencing crop yields is essential for crop management and ensuring global food security. However, comprehensive studies on the relative importance of multiple environmental factors and their interactions on crop yields during different phenological stages are still limited. In this study, we adopted a spatial heterogeneity detection method—geographic detector (GeoDetector)—to quantify how environmental factors, i.e., air pollutants, elevation, meteorological factors, and soil conditions, as well as their interactive effects, contributed to winter wheat yield. Data collected from agrometeorological stations in Henan Province, China, from 2014 to 2017 were analyzed as a case study. Results revealed that the dominant factors impacting winter wheat yield were elevation and soil acidity (pH). The interactions between elevation and soil conditions showed the strongest explanatory power throughout the growth period. Although air pollutants had relatively low independent impacts on yield, the interactions between air pollutants and other factors had significant nonlinear impacts. Contrary to traditional studies, ozone (O3 ) did not significantly impact winter wheat yield. In our study, carbon monoxide (CO) and sulfur dioxide (SO2 ) were the main air pollutants affecting yield at most growth stages, and the interactions between CO and elevation, pH, soil organic matter, and SO2 were significant. The effects of air pollutants on yield also changed across the growth stages, with the greatest impact observed from the three-leaf to tillering stages, and the weakest observed from the tillering to green-up stages. These findings improve our understanding of the relative importance of environmental factors on winter wheat yields, and have important implications for managing agricultural activities, improving crop models, and developing food security policies. Graphical abstract: Image 1 Highlights: Food security policy requires quantifying environmental influences on crops. GeoDetector was used to determine the influence of factors on winter wheat yield. Quantified effects of air pollutants, soil, elevation and meteorological factors. Enhanced interactions of air pollutants and environmental factors were quantified. Identified variations in effects of air pollutants on yields across growth stages.